Holy feast and holy fast : the religious significance of food to medieval women - Bynum, Caroline Walker (New historicism., 1987)
In the period between 1200 and 1500 in western Europe, a number of religious women gained widespread veneration and even canonization as saints for their extraordinary devotion to the Christian eucharist, supernatural multiplications of food and drink, and miracles of bodily manipulation, including stigmata and inedia (living without eating). The occurrence of such phenomena sheds much light on the nature of medieval society and medieval religion. It also forms a chapter in the history of women. Previous scholars have occasionally noted the various phenomena in isolation from each other and ha.